A mulandóság gátja . The Threshold of Transience – aka The Dike of Transience - Nemes, Gyula (Inforg Stúdió ; FAMU, 2004)
Duration: 00:13:00 Captured over three years, this black-and-white pictorial study portrays life under the threat of demolition at the Kopaszi dam. The raw image of dug-out material comes alongside mini-portraits of the inhabitants of the settlement. The mood is influenced by the work of Czech writer Bohumil Hrabal, whose poetics form a link to impressive insights into a slumbering corner of the countryside. The contribution of the sound track – a village brass band rehearsing Beethoven’s Egmont overture – permeates everything with a sorrowfully melancholy feeling of the transience of human destinies.